A prospective evaluation of clinical and instrumental features before and after ventriculo-peritoneal shunt in patients with idiopathic Normal pressure hydrocephalus: The Bologna PRO-Hydro study. (September 2019) - ,; Agati, Raffaele; Calandra-Buonaura, Giovanna; Capellari, Sabina; Parchi, Piero; Stanzani-Maserati, Michelangelo; Marliani, Anna Federica; Merola, Margherita; Piserchia, Vito Antonio; Sambati, Luisa; Sturiale, Carmelo; Supino, Antonella; et al.
Abstract: Introduction: Idiopathic Normal Pressure Hydrocephalus (iNPH) is a complex and often misdiagnosed syndrome, whose major challenge is to identify which patients will benefit from surgery. Previous studies reported a variability in positive surgery response. The role of tap test(TT) in screening patients suitable for shunting is controversial. The primary aim of this study was to describe the clinical/instrumental features and their longitudinal progression after surgery in iNPH patients. Secondarily, we aimed to investigate the response of the three iNPH domains and the best time of outcome assessment after TT. Methods: Patients compatible with iNPH underwent a 3-T-MRI and an inpatients program with TT including standardized clinical evaluations, neuropsychological assessments and instrumental gait analysis pre- and after-(24-h and 72-h) TT. The multidisciplinary team selected candidates for surgery. Patients were evaluated 6- and 12-months after surgery. Results: A total of 154 consecutive patients were included from 2015 to 2018, 76 with an iNPH diagnosis (43 underwent surgery, 35 were evaluated after 6-months). Clinical and instrumented quantitative gait measures and urinary symptoms improved over time along with some neuropsychological functions. Concerning pre- and post-TT analyses, the three iNPH domains showed a different response after TT, the delayed motor assessment was more appropriate than the early one and the instrumental measures highlighted the motor improvement. Conclusion: iNPH patients improved after surgery, when accurately selected. A multidisciplinary team focused on this disease and a standardized protocol helped in achieving a correct diagnosis and management of iNPH. Our results could impact the management of this disease. Highlights: A multidisciplinary team is important for diagnosis and management of iNPH patients. Surgery mainly improves motor and urinary symptoms. The three domains of iNPH showed a different response after Tap Test. The delayed motor assessment after Tap Test is more appropriate than the early one. Instrumental motor measures better shows the motor improvement than clinical ones.